Diffeologies and Generalized Kadomtsev-Petviashvili Hierarchies - Reyes-Garcia, E (American Mathematical Society, 2024)
We present a simplified, but extended proof of the well-posedness of the Kadomtsev-Petviashvili hierarchy of formal pseudo-differential symbols with coefficients in an abstract diffeological differential algebra, and with initial value a formal symbol of arbitrary order. © 2024 American Mathematical Society.